Activation and functional connectivity of cerebellum during reading and during arithmetic in children with combined reading and math disabilities - Ashburn, Sikoya M.; Matejko, Anna A.; Eden, Guinevere F. (Frontiers in Neuroscience, 2024)
Reading and math constitute important academic skills, and as such, reading disability (RD or developmental dyslexia) and math disability (MD or developmental dyscalculia) can have negative consequences for children's educational progress. Although RD and MD are different learning disabilities, they frequently co-occur. Separate theories have implicated the cerebellum and its cortical connections in RD and in MD, suggesting that children with combined reading and math disability (RD+MD) may have altered cerebellar function and disrupted functional connectivity between the cerebellum and cortex during reading and during arithmetic processing. Here we compared Control and RD+MD groups during a reading task as well as during an arithmetic task on (i) activation of the cerebellum, (ii) background functional connectivity, and (iii) task-dependent functional connectivity between the cerebellum and the cortex. The two groups (Control, RD+MD) did not differ for either task (reading, arithmetic) on any of the three measures (activation, background functional connectivity, task-dependent functional connectivity). These results do not support theories that children's deficits in reading and math originate in the cerebellum.